ANALYSIS OF SCHOOL LEADERSHIP STYLE IN SMP 5 SATU ATAP TELAGA BIRU KABUPATEN GORONTALO - Ester Mohamad; Azis Rachman; Maman Musa (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims to analyze the leadership style of school principals in SMP 5 SatuAtapTelagaBiru, Kabupaten Gorontalo. This type of research uses a qualitative approach. The informants in this study were 5 people, namely the Principal, Deputy Principal and Teachers in SMP 5 SatuAtapTelagaBiru. Data collection techniques, observation, interviews, documentation. The research subject was the principal. The results showed that the Principal SMP N 5 SatuAtapTelagabiruapply participatory and delegate leadership styles and do not apply authoritarian leadership styles.